PENGEMBARAAN ILMIAH DAN PERAN SYEIKH AHMAD KHATIB AL-SYAMBASI DALAM PENYEBARAN ISLAM DI NUSANTARA MELALUI THARIQAT QADIRIYYAH WA NAQSABDNIYYAH - Farisi, Salman al (Living Islam: Journal of Islamic Discourses, 2021)
Abstract This article describes the figures of the Nusantara Ulamas who ever had a network of Middle Eastern Ulamas (clerics) known as Ashabul Jawawyn, namely Sheikh Ahmad Khatib al-Sambasi, who has a very large role in the spread of Islamic teachings. He is known as an expert in the field of Sufism and is called as a Tsufi expert. He is also known as the founder of the Qadiriyyah wa Naqsbandiyyah sufism movement. In the process of collecting data, the author refers to references in the form of books, journals, articles, and other relevant sources to the purpose of writing this article. After data collection, the author then sorts and selects the suits datas used as a reference and then describes them.  In accordance with the objectives of the article in this paper, it was found that Sheikh Muhammad Ibn 'Abd Ghaffar al-Sambasi was an Nusantara cleric from West Kalimantan who wandered in search of knowledge to the Haramyn Country at the age of 19 years, and lived in Mecca until he died in In 1875. However, Sheikh Ahmad Khatib al-Syambasi was known as a person who had a big role in the Islamic world, especially some areas of the archipelago and Malay, among the roles of Sheikh Ahmad Khatib al-Sambasi was to spread Islamic teachings through the Qadiryyah wa Naqsbandiyyah order, with reference to The book that is used as a reference in this tarekat is the book of Fati h al-'Arifin a book written by his students through direct instruction from his teacher Sheikh Ahmad Khatib al-Syambasi.Keywords: Nusantara Ulama, Middle East, Ashabul Jawawyn, Sheikh Ahmad Khatib al-Sambasi, Qadiriyyah-Naqsbandiyyah.Artikel ini berusaha menguraikan tokoh ulama Nusnatara yang termasuk ke dalam jaringan ulama Timur Tengah yang dikenal dengan Ashabul Jawawyn yakni Syeikh Ahmad Khatib al-Sambasi, yang memiliki peran yang sangat besar dalam penyebaran ajaran Islam, ia dikenal sebagai seorang yang ahli dalam bidang tasawuf dan disebut sebagai ahli Tsufi, ia juga dikenal sebagai pendiri tarekat Qadiriyyah wa Naqsabandiyyah[1]. Dalam mengumpulkan data, Penulis merujuk kepada refrensi yang berupa buku-buku, Jurnal, artikel, dan lain-lainnya yang relevan dengan tujuan pada penulisan artikel ini, dan setelah data terkumpul penulis, memilah serta memilih data yang dijadikan sebagai sumber refrensi kemudian menguraikan data yang didapatkan sesuai dengan tujuan dari artikel pada tulisan ini, ditemukan bahwa Syeikh Muhammad Ibn ‘Abd Ghaffar al-Sambasi adalah seorang ulama Nusantara yang berasal dari Kalimantan Barat yang mengembara mencari Ilmu Ke Negeri Haramyn pada usia 19 Tahun, dan  menetap di Mekkah hingga ia Wafat pada tahun 1875 [2], walaupun demikian Syeikh Ahmad Khatib al-Syambasi dikenal sebagai seorang yang memiliki peran yang Besar dalam dunia Islam, khususnya beberapa wilayah Nusantara dan Melayu, diantara peran Syeikh Ahmad Khatib al-Sambasi ialah menyebarkan ajaran Islam melalui tarekat Qadiryyah wa Naqsabandiyyah, dengan mengacu kepada kitab yang dijadikan sebagai rujukan di dalam tarekat ini ialah kitab Fath al-‘Arifinkitab yang tulis oleh para muridnya melalui pendiktian langsung  dari gurunya yakni Syeikh Ahmad Khatib al-Syambasi.[1] Said Aqil Siraj, Tasawuf Sebagai Kritik Sosial : Mengedepankan Islam Sebagai Inspirasi, Bukas Aspirasi, (Bandung : Mizan Pustaka, 2006), hlm. 426.[2]  Muhammad Abdul Mujib dkk, Ensiklopedia Tasawuf Imam al-Ghazali, (Jakarta: Penerbit Hikmah, 2009),hlm.334.